Orai1 deficiency leads to heart failure and skeletal myopathy in zebrafish - Völkers, Mirko; Dolatabadi, Nima; Gude, Natalie; Most, Patrick; Sussman, Mark A.; Hassel, David (Journal of cell science, 2012)
Mutations in the store-operated Ca2+ entry pore protein ORAI1 have been reported to cause myopathies in human patients but the mechanism involved is not known. Cardiomyocytes express ORAI1 but its role in heart function is also unknown. Using reverse genetics in zebrafish, we demonstrated that inactivation of the highly conserved zebrafish orthologue of ORAI1 resulted in severe heart failure, reduced ventricular systolic function, bradycardia and skeletal muscle weakness. Electron microscopy of Orai1-deficient myocytes revealed progressive skeletal muscle instability with loss of myofiber integrity and ultrastructural abnormalities of the z-disc in both skeletal and cardiac muscle. Isolated Orai1-deficient cardiomyocytes showed loss of the calcineurin-associated protein calsarcin from the z-discs. Furthermore, we found mechanosignal transduction was affected in Orai1-depleted hearts, indicating an essential role for ORAI1 in establishing the cardiac signaling transduction machinery at the z-disc. Our findings identify ORAI1 as an important regulator of cardiac and skeletal muscle function and provide evidence linking ORAI1-mediated calcium signaling to sarcomere integrity and cardiomyocyte function.